Poly(trimethylene carbonate)/Poly(malic acid) Amphiphilic Diblock Copolymers as Biocompatible Nanoparticles. Issue 8 (21st January 2016) - Barouti, Ghislaine; Khalil, Ali; Orione, Clement; Jarnouen, Kathleen; Cammas‐Marion, Sandrine; Loyer, Pascal; Guillaume, Sophie M.
Abstract: Amphiphilic polycarbonate–poly(hydroxyalkanoate) diblock copolymers, namely, poly(trimethylene carbonate) (PTMC)‐ b ‐poly(β‐malic acid) (PMLA), are reported for the first time. The synthetic strategy relies on commercially available catalysts and initiator. The controlled ring‐opening polymerization (ROP) of trimethylene carbonate (TMC) catalyzed by the organic guanidine base 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD), associated with i PrOH as an initiator, provided i PrO−PTMC−OH, which served as a macroinitiator in the controlled ROP of benzyl β‐malolactonate (MLABe) catalyzed by the neodymium triflate salt (Nd(OTf)3 ). The resulting hydrophobic i PrO−PTMC‐ b ‐PMLABe−OH copolymers were then hydrogenolyzed into the parent i PrO−PTMC‐ b ‐PMLA−OH copolymers. A range of well‐defined copolymers, featuring different sizes of segments ( M n, NMR up to 9300 g mol −1 ; Ð M =1.28–1.40), were thus isolated in gram quantities, as evidenced by NMR spectroscopy, size exclusion chromatography, thermogravimetric analysis, differential scanning calorimetry, and contact angle analyses. Subsequently, PTMC‐ b ‐PMLA copolymers with different hydrophilic weight fractions (11–75 %) self‐assembled in phosphate‐buffered saline upon nanoprecipitation into well‐defined nano‐objects with D h =61–176 nm, a polydispersity index <0.25, and a negative surface charge, as characterized by dynamic light scattering and zeta‐potential analyses. In addition, these nanoparticles demonstrated no significant effect on cell viability at low concentrations, and a very low cytotoxicity at high concentrations only for PTMC‐ b ‐PMLA copolymers exhibiting hydrophilic fractions over 47 %, thus illustrating the potential of these copolymers as promising nanoparticles. Abstract : Building blocks : Amphiphilic polycarbonate–polyhydroxyalkanoate diblock copolymers, namely, poly(trimethylene carbonate) (PTMC)‐ b ‐poly(β‐malic acid) (PMLA), are reported for the first time. The synthetic strategy relies on commercially available catalysts and initiator for ring‐opening polymerization (ROP) followed by hydrogenolysis (see figure).